Use of expanded polytetrafluoroethylene grafts in the prevention of peridural fibrosis: An experimental study - Özveren, M.F.; Türkmen, C.S.; Tanik, C.; Ziyal, I.M.; Erol, F.S. (Turkish Neurosurgical Society, 2001)
The aim of this study was to investigate whether expanded polytetrafluoroethylene (ePTFE) grafts prevent peridural fibrosis (PF). Seven adult dogs were anesthetized with an intramuscular injection of xylazine + ketamine HCl, and were operated on between L5 and S1 via a posterior approach. Total laminectomies were performed at L5, L6, and L7, and the spinal dura mater and associated tissues from L5 to S1 were exposed. In the control region of the spine (L5-L6), we performed a discectomy and removed the ligamentum flavum and epidural fat. In the next section (L6-L7), we performed a discectomy but left the ligamentum flavum and epidural fat tissue intact, forming a pediculated fat graft in the laminectomy defect. At L7-S1, we performed the same procedures as were done at the previous level, but inserted an ePTFE graft in place of the ligamentum flavum and fat graft. Three dogs were sacrificed after 3 months, another two dogs after 6 months, and the last two after 9 months. Histopathological evaluation of tissues from the animals sacrificed at 3 months revealed +3 grade PF at the control level, and +2 grade PF at the level with the preserved ligamentum flavum and fat graft in all three dogs. At the ePTFE graft level, two animals showed + 2 grade PF and one showed +1 grade PF. Specimens from the four dogs sacrificed at 6 and 9 months showed +3 grade PF at all levels. The results demonstrated that ePTFE grafts do not effectively prevent PF throughout the 9-month period after laminectomy with discectomy.
Keywords: Expanded polytetrafluoroethylene graft; Fat graft; Laminectomy membrane; Peridural fibrosis